RESEARCH STATUS OF SMART ROLLING BEARING MONITORING METHODS - CHEN JinHai; LI Wei; ZHANG WenYuan; WANG Heng (Jixie qiangdu)
Smart bearing is a structural unit of bearing set sensor. It has the characteristics of self-sensing,self-diagnosis,self-adaptation and self-regulation. It is one of the development directions of high-end bearing development at home and abroad.Firstly,Expounded the concept and key technologies of smart bearings. Secondly,the advantages and disadvantages of external smart bearing and embedded intelligent bearing are summarized. It is considered that embedded structure is the main direction of future research of smart bearing. According to the requirements of rolling bearing condition monitoring and diagnosis,the current application of smart bearing sensors,such as acceleration sensors,temperature sensors,lubricating oil quality detection sensors,torque sensors,and thin film sensors,are introduced. Finally,the development trend of smart rolling bearing monitoring technology is summarized and forecasted.